Basics and prospective of magnetic Heusler compounds - Felser, Claudia; Wollmann, Lukas; Chadov, Stanislav; Fecher, Gerhard H.; Parkin, Stuart S. P. (APL Materials, 2015)
Heusler compounds are a remarkable class of materials with more than 1000 members and a wide range of extraordinary multi-functionalities including halfmetallic high-temperature ferri- and ferromagnets, multi-ferroics, shape memory alloys, and tunable topological insulators with a high potential for spintronics, energy technologies, and magneto-caloric applications. The tunability of this class of materials is exceptional and nearly every functionality can be designed. Co2-Heusler compounds show high spin polarization in tunnel junction devices and spin-resolved photoemission. Manganese-rich Heusler compounds attract much interest in the context of spin transfer torque, spin Hall effect, and rare earth free hard magnets. Most Mn2-Heusler compounds crystallize in the inverse structure and are characterized by antiparallel coupling of magnetic moments on Mn atoms; the ferrimagnetic order and the lack of inversion symmetry lead to the emergence of new properties that are absent in ferromagnetic centrosymmetric Heusler structures, such as non-collinear magnetism, topological Hall effect, and skyrmions. Tetragonal Heusler compounds with large magneto crystalline anisotropy can be easily designed by positioning the Fermi energy at the van Hove singularity in one of the spin channels. Here, we give a comprehensive overview and a prospective on the magnetic properties of Heusler materials.
CRIS-Team Scopus Importer:2023-03-20